2013
DOI: 10.1002/ddr.21158
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Curcumin Derivatives as Potential Chemotherapeutic and Antioxidant Agents

Abstract: The purpose of this work was to synthesize a series of symmetrical analogs (CA2-CA7) of curcumin and determine their efficacy as antioxidant and anticancer agents in vitro. The six analogs were successfully synthesized and characterized, one of which, CA6, had not been previously reported in the literature. With the exception of CA2, the analogs had lower predicted aqueous solubilities and higher partition coefficients than curcumin. Two analogs, CA2 and CA3, had lower potencies as anticancer agents compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…1c ). This is consistent with previous study which showed that the alkylation of ortho-phenolic OH group in curcumin and its derivatives can increase its anti-cancer activity 14 . However, all the OH modified derivatives share the same pharmacophore (α, β-unsaturated ketone group) which imply they have same mode of action 15 16 .…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…1c ). This is consistent with previous study which showed that the alkylation of ortho-phenolic OH group in curcumin and its derivatives can increase its anti-cancer activity 14 . However, all the OH modified derivatives share the same pharmacophore (α, β-unsaturated ketone group) which imply they have same mode of action 15 16 .…”
Section: Resultssupporting
confidence: 94%
“…Previous studies showed that the α, β-unsaturated ketone group of curcumin is critical for its biological activity 3 4 . Structure-activity relationship studies suggested that the derivative of curcumin at the hydroxyl group did not affect the active moiety of the drug 1 14 . To profile and identify the direct targets of curcumin, we introduced an alkyne group at the hydroxyl group position of curcumin to synthesize an activity-based probe, which enables the subsequent linking with a fluorescent dye or biotin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Its potency was determined due to the morphological changes in SKOV3 cell lines and apoptotic cell death by arresting the cells in S and G2/M phases. In addition, six symmetric curcumin analogues by Ciochina et al (2014) were synthesised by the condensation of the appropriate aldehydes with acetyl acetone-boric oxide complex in ethyl acetate in the presence of tributyl borate and n-butylamine. The analogues were investigated for their antioxidant and anticancer activity, where compounds 11 and 12 demonstrated a greater potential to be chemopreventive agents due to their low cytotoxic potential (Ciochina et al, 2014) 17) and reported its anticancer properties against MCF-7 breast cancer cells which confirmed cell death through cell cycle arrest and induction of apoptosis.…”
Section: Scheme 1 Structural Analogues Of Curcumin (1-8)mentioning
confidence: 99%
“…Another approach is the synthesis of novel analogs of nutraceuticals. A number of analogs of various nutraceuticals have been reported [ 40 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. This is another effective strategy to improve the efficacy of nutraceuticals by chemically modifying the structure of the compound, leading to enhanced cytotoxicity, as evidenced by lowered IC 50 values.…”
Section: Nutraceuticals As Anticancer Agents: Challengesmentioning
confidence: 99%